Analisis Nilai Sosial, Fungsional, Emosional, Kepuasan, dan Identifikasi Karakter yang Mempengaruhi Intensi Pembelian Barang Virtual pada Game Online - Virgian Tengara Jati; Ambar Lukitaningsih; Nonik Kusuma Ningrum (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine (1) whether sosial value has a positive effect on purchase intention, (2) to determine whether functional value has a positive effect on purchase intention, (3) to determine whether emotional value has a positive effect on purchase intention, (4) to determine whether whether satisfaction has a positive effect on purchase intentions, (5) to find out whether character identification has a positive effect on bell intentions. This type of research includes quantitative descriptive research. The population in this study were all players or users of Massively Multiplayer Sosializer Online Games (MMOSG), Audition Ayodance). The method used in the selection of the sample is purposive sampling method and determine the sample based on the criteria set by the researcher. There were 190 questionnaires distributed which could be processed. The data is then tested for data quality by using the validity test, reliability test. After testing the quality of the data, it is then tested using the classical multiple regression assumption test. The classical assumption test used consisted of normality test, multicollinearity test and heteroscedasticity test. Then the data were analyzed using the coefficient of determination test, partial test (t) and simultaneous test (f). The results of this study indicate that there is a negative and insignificant effect of Sosial Value on Purchase Intention (1) there is a positive and significant influence of Functional Value on Purchase Intention (2) there is a positive influence of Emotional Value on Purchase Intention (3) there is a negative and insignificant effect of Satisfaction on Purchase Intention (4) and there is a positive and significant effect of Character Identification on Purchase Intention (5) the players or users of Massively Multiplayer Sosializer Online Games (MMOSG), Audition Ayodance.